Find the equation of the tangent line to the circle ${{(x+2)}^{2}}+{{(y-3)}^{2}}=25$ at the point $A$ $(-5,7)$.
Answer
Verified
511.5k+ views
Hint: Assume a line with a variable slope, passing through the point $(-5,7)$ and then make the perpendicular distance of the centre of the circle equal to the radius of the circle, to get the slope, and eventually the tangent.
First, let’s analyse the equation of the circle given to us :
${{(x+2)}^{2}}+{{(y-3)}^{2}}=25$, by comparing it to the general equation of a circle which is ${{(x+g)}^{2}}+{{(y+f)}^{2}}={{r}^{2}}$, where the centre of the circle is $(-g,-f)$ and the radius of the circle is $r$.
Comparing the equation given to us with the general equation, we get :
$g=2,f=-3,r=\sqrt{25}=5$
Thus, the centre of this circle is = $(-g,-f)=(-2,3)$ and its radius $=5$
Now, to find the tangent passing through the point $A$, let’s assume a line whose equation can be written as :
$\begin{align}
& \dfrac{y-7}{x+5}=m \\
& \Rightarrow y-7=mx+5m \\
& \Rightarrow y=mx+5m+7 \\
& \Rightarrow mx-y+(5m+7)=0 \\
\end{align}$
since it’s mandatory for the tangent to pass through point $A$, and this is how the equation of a line passing through a given point is written as.
Let’s call this equation of tangent in terms of $m$ as (1).
Now, we know that the tangent is perpendicular to the line joining the centre of the circle to the point where the tangent touches the circle. This means that the tangent is perpendicular to the line representing the radius of the circle at the point $A$.
This implies that the perpendicular distance of the centre of the circle from the tangent will be equal to the circle’s radius.
$\Rightarrow d=r$ where $d$ is the perpendicular distance of the centre from (1) and $r$ is the circle’s radius.
The formula to find the perpendicular distance of a point $(X,Y)$ from a line $Ax+By+C=0$ is :
$d=\dfrac{|AX+BY+C|}{\sqrt{{{A}^{2}}+{{B}^{2}}}}$
Here, the point we have to find the perpendicular distance for is the centre $(-g,-f)=(-2,3)$ , and the line we have to find it from is (1) or $mx-y+(5m+7)=0$
$\begin{align}
& \Rightarrow d=\dfrac{|AX+BY+C|}{\sqrt{{{A}^{2}}+{{B}^{2}}}} \\
& \Rightarrow d=\dfrac{|-2m-3+5m+7|}{\sqrt{{{m}^{2}}+1}} \\
\end{align}$
But, we know that for this question, $d=r=5$
$\begin{align}
& \Rightarrow r=\dfrac{|3m+4|}{\sqrt{{{m}^{2}}+1}} \\
& \Rightarrow 5=\dfrac{|3m+4|}{\sqrt{{{m}^{2}}+1}} \\
\end{align}$
Squaring both sides, we get :
$\begin{align}
& \Rightarrow 25=\dfrac{{{(3m+4)}^{2}}}{{{m}^{2}}+1} \\
& \Rightarrow 25({{m}^{2}}+1)=9{{m}^{2}}+16+24m \\
& \Rightarrow 25{{m}^{2}}+25=9{{m}^{2}}+16+24m \\
& \Rightarrow 16{{m}^{2}}-24m+9=0 \\
& \Rightarrow 16{{m}^{2}}-12m-12m+9=0 \\
& \Rightarrow 4m(4m-3)-3(4m-3)=0 \\
& \Rightarrow {{(4m-3)}^{2}}=0 \\
& \Rightarrow m=\dfrac{3}{4} \\
\end{align}$
Substituting the value of $m$ obtained in (1), we get the final equation of the tangent as :
$\begin{align}
& mx-y+(5m+7)=0 \\
& \Rightarrow \dfrac{3}{4}x-y+(5\times \dfrac{3}{4}+7)=0 \\
& \Rightarrow \dfrac{3}{4}x-y+\dfrac{43}{4}=0 \\
& \Rightarrow 3x-4y+43=0 \\
\end{align}$
Here’s a diagram to ease your understanding :
As you can see, eq2 is the tangent to the circle with eq1, and it is a tangent at the point $A=(-5,7)$.
Hence, our final equation of the tangent to ${{(x+2)}^{2}}+{{(y-3)}^{2}}=25$ at the point $A$ $(-5,7)$ is $3x-4y+43=0$.
So the answer to the required equation is $3x-4y+43=0$.
Note: Be careful while working with modulus. While squaring a modulus, we can simply square the expression that’s present inside the modulus, rather than considering both the positive and negative possibilities of the expression. This is because whatever the expression is, the square of a negative number and a positive number of the same magnitude, are always equal. Thus, we can simply square the expression inside the modulus, without having to worry about the sign.
First, let’s analyse the equation of the circle given to us :
${{(x+2)}^{2}}+{{(y-3)}^{2}}=25$, by comparing it to the general equation of a circle which is ${{(x+g)}^{2}}+{{(y+f)}^{2}}={{r}^{2}}$, where the centre of the circle is $(-g,-f)$ and the radius of the circle is $r$.
Comparing the equation given to us with the general equation, we get :
$g=2,f=-3,r=\sqrt{25}=5$
Thus, the centre of this circle is = $(-g,-f)=(-2,3)$ and its radius $=5$
Now, to find the tangent passing through the point $A$, let’s assume a line whose equation can be written as :
$\begin{align}
& \dfrac{y-7}{x+5}=m \\
& \Rightarrow y-7=mx+5m \\
& \Rightarrow y=mx+5m+7 \\
& \Rightarrow mx-y+(5m+7)=0 \\
\end{align}$
since it’s mandatory for the tangent to pass through point $A$, and this is how the equation of a line passing through a given point is written as.
Let’s call this equation of tangent in terms of $m$ as (1).
Now, we know that the tangent is perpendicular to the line joining the centre of the circle to the point where the tangent touches the circle. This means that the tangent is perpendicular to the line representing the radius of the circle at the point $A$.
This implies that the perpendicular distance of the centre of the circle from the tangent will be equal to the circle’s radius.
$\Rightarrow d=r$ where $d$ is the perpendicular distance of the centre from (1) and $r$ is the circle’s radius.
The formula to find the perpendicular distance of a point $(X,Y)$ from a line $Ax+By+C=0$ is :
$d=\dfrac{|AX+BY+C|}{\sqrt{{{A}^{2}}+{{B}^{2}}}}$
Here, the point we have to find the perpendicular distance for is the centre $(-g,-f)=(-2,3)$ , and the line we have to find it from is (1) or $mx-y+(5m+7)=0$
$\begin{align}
& \Rightarrow d=\dfrac{|AX+BY+C|}{\sqrt{{{A}^{2}}+{{B}^{2}}}} \\
& \Rightarrow d=\dfrac{|-2m-3+5m+7|}{\sqrt{{{m}^{2}}+1}} \\
\end{align}$
But, we know that for this question, $d=r=5$
$\begin{align}
& \Rightarrow r=\dfrac{|3m+4|}{\sqrt{{{m}^{2}}+1}} \\
& \Rightarrow 5=\dfrac{|3m+4|}{\sqrt{{{m}^{2}}+1}} \\
\end{align}$
Squaring both sides, we get :
$\begin{align}
& \Rightarrow 25=\dfrac{{{(3m+4)}^{2}}}{{{m}^{2}}+1} \\
& \Rightarrow 25({{m}^{2}}+1)=9{{m}^{2}}+16+24m \\
& \Rightarrow 25{{m}^{2}}+25=9{{m}^{2}}+16+24m \\
& \Rightarrow 16{{m}^{2}}-24m+9=0 \\
& \Rightarrow 16{{m}^{2}}-12m-12m+9=0 \\
& \Rightarrow 4m(4m-3)-3(4m-3)=0 \\
& \Rightarrow {{(4m-3)}^{2}}=0 \\
& \Rightarrow m=\dfrac{3}{4} \\
\end{align}$
Substituting the value of $m$ obtained in (1), we get the final equation of the tangent as :
$\begin{align}
& mx-y+(5m+7)=0 \\
& \Rightarrow \dfrac{3}{4}x-y+(5\times \dfrac{3}{4}+7)=0 \\
& \Rightarrow \dfrac{3}{4}x-y+\dfrac{43}{4}=0 \\
& \Rightarrow 3x-4y+43=0 \\
\end{align}$
Here’s a diagram to ease your understanding :
As you can see, eq2 is the tangent to the circle with eq1, and it is a tangent at the point $A=(-5,7)$.
Hence, our final equation of the tangent to ${{(x+2)}^{2}}+{{(y-3)}^{2}}=25$ at the point $A$ $(-5,7)$ is $3x-4y+43=0$.
So the answer to the required equation is $3x-4y+43=0$.
Note: Be careful while working with modulus. While squaring a modulus, we can simply square the expression that’s present inside the modulus, rather than considering both the positive and negative possibilities of the expression. This is because whatever the expression is, the square of a negative number and a positive number of the same magnitude, are always equal. Thus, we can simply square the expression inside the modulus, without having to worry about the sign.
Recently Updated Pages
What percentage of the area in India is covered by class 10 social science CBSE
The area of a 6m wide road outside a garden in all class 10 maths CBSE
What is the electric flux through a cube of side 1 class 10 physics CBSE
If one root of x2 x k 0 maybe the square of the other class 10 maths CBSE
The radius and height of a cylinder are in the ratio class 10 maths CBSE
An almirah is sold for 5400 Rs after allowing a discount class 10 maths CBSE
Trending doubts
The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths
Why is there a time difference of about 5 hours between class 10 social science CBSE
Change the following sentences into negative and interrogative class 10 english CBSE
Write a letter to the principal requesting him to grant class 10 english CBSE
Explain the Treaty of Vienna of 1815 class 10 social science CBSE
Write an application to the principal requesting five class 10 english CBSE